Spontaneous Ocular Haemorrhage: Poster Presentation - Case Report - General practitioner - Klarissa Chrishalim; Cisca Kuswidyati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Hemorrhagic complications are one of the major complications encountered with reperfusion therapies but rarely involve the ocular, especially hyphema. Case Illustration : a 61-year-old woman presented with blurred vision, discomfort, and red eye in her right eye. She had been treated for hypertension, diabetes mellitus, and coronary artery disease with antiplatelet and other oral medication for 5 years. There was no history of eye trauma or Valsalva-like maneuver effort. The best corrected visual acuity was 20/40 in both eyes and there was no relative afferent pupillary defect. Both eyes had normal IOP. A slit lamp examination revealed pool blood in the anterior chamber as hyphema grade 1. Fundus examination showed dot and blot hemorrhage with cupping discs 0.6 and 0.7. USG examination showed no mass and clear vitreous. The antiplatelet was stopped and evaluated by the internal department. The patient was observed and treated with topical medication, and the hyphema resolved within less than 7 days. Discussion : Although it is still not clear if there is any increase in intraocular bleeding has been recognized with antiplatelet agents, the concern would be greatest amongst those at high baseline risk due to predisposing conditions, such as elderly with diabetes, hypertension, and usage of antiplatelet agents to maintain cardiovascular disease. Conclusion : This case emphasizes that though the most common cause of hyphema is a traumatic injury, it can be a rare complication of antiplatelet therapy. Patients on antiplatelet therapy should be carefully monitored for ocular bleeding, especially if they have associated systemic or ocular comorbidity.